Sandmeyer Chlorosulfonylation of (Hetero)Aromatic Amines Using DABSO as an SO 2 Surrogate - Pincekova, L; Merot, A; Schäfer, G; Willis, MC (American Chemical Society, 2024)
Sulfonyl chlorides not only play a crucial role in protecting group chemistry but also are important starting materials in the synthesis of sulfonamides, which are in-demand motifs in drug discovery chemistry. Despite their importance, the number of different synthetic approaches to sulfonyl chlorides is limited, and most of them rely on traditional oxidative chlorination chemistry from thiol precursors. In this report, we disclose a novel Sandmeyer-type sulfonyl chloride synthesis from feedstock anilines and DABSO, used as a stable SO2 surrogate, in the presence of HCl and a Cu catalyst. The method works on a wide range of anilines and allows for the isolation of the sulfonyl chloride after aqueous workup or its direct conversion into the sulfonamide by simple addition of an amine after the completion of the Sandmeyer reaction. The scalability of this method was demonstrated on a 20 g scale, and the corresponding heterocyclic sulfonyl chloride was isolated in 80% yield and excellent purity.